Fresh Seminal Attributes of Surti Bucks and their Interrelationships - Bhut, Darshita V; Khasatiya, Chandubhai T; Singh, Virendra K; Sharma, Hitendra C (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The study was conducted to evaluate fresh seminal attributes of Surti bucks and their interrelationships. Fresh semen was collected  from four Surti bucks twice a week for 8 weeks, i.e., 64 ejaculates (16/buck). Ejaculates of 4 bucks were pooled and extended with  TEYCG extender. Fresh semen was observed pale yellow having mean pH of 6.8. The overall mean semen volume, density, mass activity/ motility, sperm concentration and total sperm count/ejaculate were 0.50±0.02 mL, 3.39±0.08, 3.45±0.09, 4032.81±34.00 millions/mL and  1986.25±86.03 million, respectively. Percentages of individual sperm motility, live sperms, abnormal sperms and HOST reacted sperms  in pooled extended Surti bucks semen were 80.63±1.76, 83.06±1.64, 9.56±0.47 and 78.06±0.96. Ejaculate volume and total sperm count  significantly (p
Keywords: Fresh seminal attributes; Interrelationships; Surti buck.